2020
DOI: 10.3168/jds.2019-17194
|View full text |Cite
|
Sign up to set email alerts
|

Decreased amylolytic microbes of the hindgut and increased blood glucose implied improved starch utilization in the small intestine by feeding rumen-protected leucine in dairy calves

Abstract: Starch digestion in the small intestine in ruminants is relatively lower compared with that in monogastric animals, likely due to low pancreatic α-amylase secretion. Previous studies suggested that leucine could increase pancreatic α-amylase secretion in the small intestine of heifers cannulated with abomasal, duodenal, and ileal catheters. However, the surgical procedures probably have an effect on pancreatic function. Thus, we used rumen-protected leucine (RP-Leu) to explore its effect on small intestinal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The newborn hindgut microbiome plays important metabolic and nutritional functions (1), with one of its main roles being the development of the intestinal barrier (2) and the maturation of the innate immune system in early life (3). Available studies in humans, lambs, and foals have focused on understanding the hindgut microbiome when microbial colonization starts (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The newborn hindgut microbiome plays important metabolic and nutritional functions (1), with one of its main roles being the development of the intestinal barrier (2) and the maturation of the innate immune system in early life (3). Available studies in humans, lambs, and foals have focused on understanding the hindgut microbiome when microbial colonization starts (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…criteria(20):(1) single calf; (2) calving difficulty score <3;(3) dam's colostrum quality assessed by a bovine colostrometer (HT-113ATC, Hengan Electronic Technology Co., China) of >50 mg/mL of IgG; (4) dam produced at least 3.8 L of goodquality first colostrum; and (5) calf birth weight >36 kg. Related information about cow-calf is shown in…”
mentioning
confidence: 99%
“…Leucine, isoleucine, and valine are a group of EAA collectively referred to as branchedchain amino acids (BCAAs). It has been shown that leucine increased pancreatic α-amylase secretion in the SI of heifers cannulated with abomasal, duodenal, and ileal catheters (Ren et al 2020). In that study, Leu had no effects on rumen fermentation profile or starch digestibility, but blood glucose concentration and fecal-pH increased.…”
Section: Leucine Isoleucine and Valinementioning
confidence: 79%
“…The paired-end reads were quality-filtered, assembled, and trimmed as described previously [ 27 ]. The trimmed sequences were clustered into operational taxonomic units (OTUs) at ≥ 97% sequence similarity using Uclust in QIIME [ 28 ].…”
Section: Methodsmentioning
confidence: 99%